2019
DOI: 10.1093/cdn/nzz029.or05-07-19
|View full text |Cite
|
Sign up to set email alerts
|

Macular Carotenoids, Retinal Morphometry, and Cognitive Function in Multiple Sclerosis (OR05-07-19)

Abstract: Objectives Individuals with multiple sclerosis (MS) often suffer a progressive loss in visual and cognitive function. While the exact reason for the cognitive decline in MS is unknown, generalized neurodegeneration of the central nervous system has been associated with lower carotenoid levels. Carotenoids have antioxidant effects that could support nerve health and be protective against cognitive decline. Carotenoids are also found in high concentration within the center of the retina, or mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Islamian and Mehrali [ 32 ] suggested that carotenoids have excellent free radical and singlet oxygen quenching capacity. This phenomenon is associated with the inhibition of many free radical influenced diseases namely, atherosclerosis-related cardiovascular diseases [ 33 ], multiple sclerosis [ 34 ], degenerative diseases [ 35 ], and macular degeneration [ 36 ]. Graff et al [ 37 ] showed a positive relationship between the consumption of tomato sauce and lycopene and the reduction of prostate cancer.…”
Section: Sources Of Bioactive Compoundsmentioning
confidence: 99%
“…Islamian and Mehrali [ 32 ] suggested that carotenoids have excellent free radical and singlet oxygen quenching capacity. This phenomenon is associated with the inhibition of many free radical influenced diseases namely, atherosclerosis-related cardiovascular diseases [ 33 ], multiple sclerosis [ 34 ], degenerative diseases [ 35 ], and macular degeneration [ 36 ]. Graff et al [ 37 ] showed a positive relationship between the consumption of tomato sauce and lycopene and the reduction of prostate cancer.…”
Section: Sources Of Bioactive Compoundsmentioning
confidence: 99%
“…The two main classes of carotenoids are xanthophylls (yellow color) that contain oxygen and carotenes (orange color) that consist of linear hydrocarbons, which can cyclize at both ends of the molecule [71]. Carotene supplementation is related to the inhibition of atherosclerosisrelated multiple sclerosis [264], cardiovascular diseases [265], macular degeneration [266], and degenerative diseases [267]. Carotenes are most bioavailable in their natural transform [268,269].…”
Section: Carotenoids From Agri-food Wastementioning
confidence: 99%
“…Carbon dioxide is suitable for the extraction of lipophilic compounds since it has a polarity similar to pentane as well as other desirable characteristics such as being non-flammable, non-toxic, available in high purity, and easily removed from the extract, as well as having low temperature (32 • C) and critical pressure (74 bar). Favorable extraction conditions are related to the solubility of essential oil compounds in supercritical CO 2 [264], the plant's pretreatment (used to facilitate the extraction by improving solvent contact and breaking cells), and online fractionation (used to achieve the separation of the essential oil from cuticular waxes) [280]. Essential oils from Lamiaceae (e.g., oregano, thyme, rosemary, sage, basil, and marjoram) and citrus (e.g., lemon, orange, etc.)…”
Section: Essential Oil From Agri-food Wastementioning
confidence: 99%